Pneumatosis Intestinalis Predictive Evaluation Study: A multicenter epidemiologic study of the American Association for the Surgery of Trauma. Issue 3 (March 2017) - Ferrada, Paula; Callcut, Rachael; Bauza, Graciela; O'Bosky, Karen R.; Luo-Owen, Xian; Mansfield, Nicky J.; Inaba, Kenji; Pasley, Jason; Bugaev, Nikolay; Pereira, Bruno; Moore, Forrest O.; Han, Jinfeng; et al.
Abstract : BACKGROUND: Our group has previously published a retrospective review defining variables predictive of transmural bowel ischemia in the setting of pneumatosis intestinalis (PI). We hypothesize this prospective study will confirm the findings of the retrospective review, enhancing legitimacy to the predictive factors for pathologic PI previously highlighted. METHODS: Data were collected using the Research Electronic Data Capture. Forward logistic regression was utilized to identify independent predictors for pathologic PI. Statistical significance was defined as p ⩽ 0.05. RESULTS: During the 3-year study period, 127 patients with PI were identified. Of these, 79 had benign disease, and 49 pathologic PI defined by the presence of transmural ischemia during surgical exploration or autopsy. Laboratory values such as elevated international normalized ratio (INR), decreased hemoglobin, and a lactate value of greater than 2.0 mmol/L were predictive of pathologic PI, as well as clinical factors including adynamic ileus, peritoneal signs on physical examination, sepsis, and hypotension. The location was also a significant factor, as patients with small bowel PI had a higher incidence of transmural ischemia than colonic PI. On multiple logistic regression, lactate value of greater than 2.0 mmol/L (odds ratio, 5.1, 1.3–19.5; p = 0.018), elevated INR (odds ratio, 3.2, 1.1–9.6; p = 0.031), peritonitis (15.0, 2.9–78; p = 0.001), and decreased hemoglobin (0.70, 0.50–0.97, 0.031) remained significant predictors of transmural ischemia (area under the curve, 0.90; 0.83–0.97). A lactate value of 2.0 mmol/L or greater and peritonitis are common factors between the retrospective review and this prospective study. CONCLUSIONS: We recommend surgical exploration to be strongly considered for those PI patients presenting also with a lactate greater than 2 mmol/L and/or peritonitis. We suggest strong suspicion for necrosis in those patient with PI and small bowel involvement, ascites on computed tomography scan, adynamic ileus, anemia, and a high INR. LEVEL OF EVIDENCE: Prognostic study, level II; therapeutic study, level II. Abstract : Supplemental digital content is available in the text.